1055 MALMÖ POTS SYMPTOM SCORE: ASSESSING SYMPTOM BURDEN IN POSTURAL ORTHOSTATIC TACHYCARDIA SYNDROME. (15th December 2022) - Spahic, Jasmina Medic; Hamrefors, Viktor; Johansson, Madeleine; Ricci, Fabrizio; Melander, Olle; Sutton, Richard; Fedorowski, Artur
Abstract: Background: Postural orthostatic tachycardia syndrome (POTS) is a common cardiovascular autonomic disorder characterized by excessive heart rate increase on standing and symptoms of orthostatic intolerance, posing significant limitations on functional capacity. No objective tool exists to classify symptom burden in POTS. Methods: We conducted a case-control study in 62 POTS patients and 50 healthy controls to compare symptom burden between groups using the newly developed, self-rating, 12-item, Malmö POTS Score (MAPS; 0-10 per item, total range 0-120) based on patients' own perception of symptoms through visual analogue scale assessment. We have also explored correlations between symptom severity assessed by MAPS, basic clinical parameters and postural haemodynamic changes. Results: POTS patients showed significantly higher total MAPS score (78±20 vs. 14±12, p<0.001), higher baseline systolic blood pressure (BP), diastolic BP and heart rate (HR)(p<0.001) compared with healthy controls. The most prominent symptoms in POTS were palpitations, fatigue, and concentration difficulties. Haemodynamic parameters on standing were significantly correlated with palpitations in POTS after adjustment for age and sex (lower systolic and diastolic BP, and higher HR) (p<0.001 for all). Orthostatic HR was significantly associated with concentration difficulties and total MAPS score. The optimal cut-point value of MAPS to differentiate POTS and healthy controls was ≥42 (sensitivity, 97%; specificity, 98%). Conclusions: Symptom severity, as assessed by MAPS score, is 5-fold higher in POTS compared with healthy individuals. The new MAPS score can be useful as a semi-quantitative system to assess symptom burden, monitor disease progression and evaluate pre-test likelihood of disease.